Nilai Budaya dalam Tradisi Uler-Uleran di Jungsemi Wedung Demak - Tathmainnul, Faizuna; Miftah M. Nur , Dany; Rafi Alfaris, Muh (TAMADDUN, 2024)
It is common knowledge that this rich Indonesia holds a wide variety of cultures and religious ceremonies from Sabang Island to Merauke Island. Uler-Uleran is classified as a Javanese tradition that is still carried out and preserved by the people of Jungsemi Village. The following article will explore more about the cultural values in the Uler-Uleran Tradition. The author will examine the procession, cultural values in the Uler-Uleran Tradition, and the dynamics and challenges in grounding the tradition. The research method used by the researcher is literature study. The results of this study explain that first, this tradition existed before Islam developed rapidly in the land of Jungsemi. Second, this tradition has cultural values in the form of worship values, brotherhood values, tawhid values, and responsibility values. Third, the dynamics and challenges in preserving the Uler-Uleran Tradition. The dynamics: shifts in meaning, changes in implementation, and religious influences. The challenges: the influence of modernization, shifting values, loss of original meaning, and the lack of involvement of village youth.